Issues And Challenges Of Online Shoppingactivities On The Impact Of Corona Pandemic :A Study On Malaysia Retail Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The retail industries are among the prominent casualties of the COVID-19 pandemic, as people adjust to the new normal of online shopping and working from home, which has lowered demand and business volume of the industry in the short term. Due to online initiatives and lower business volume, businesses are considering downsizing wherever possible as people adapt to the new norm. New approaches to shopping, which leveraging technology and increase consumers' desire for lifestyle experiences while shopping, are currently posing a challenge to traditional shopping. Therefore, this paper aims to provide an overview on the issue and challenges of online shopping activities on the impact of Pandemic Covid-19.